2018
DOI: 10.1038/s41419-018-1153-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-139-3p regulates osteoblast differentiation and apoptosis by targeting ELK1 and interacting with long noncoding RNA ODSM

Abstract: Recent studies have confirmed that microRNAs and lncRNAs can affect bone cell differentiation and bone formation. In this study, miR-139-3p was upregulated in the femurs of hindlimb unloading mice and MC3T3-E1 cells under simulated microgravity; this effect was related to osteoblast differentiation and apoptosis. Silencing miR-139-3p attenuated the suppression of differentiation and the promotion of MC3T3-E1 cell apoptosis induced by simulated microgravity. ELK1 is a target of miR-139-3p and is essential for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…Our previous experiments confirmed that lncRNA ODSM and miR-139-3p interact with and repress each other 27 . By using the online lncRNA location prediction software lncLocator (http://www.csbio.sjtu.edu.cn/bioinf/ lncLocator/) and cell fractionation followed by quantitative reverse transcription polymerase chain reaction (qRT-PCR), we identified that lncRNA ODSM expression was located in the cytoplasm and nuclei of cells (Supplementary Fig.…”
Section: Lncrna Odsm Interacts With Mir-139-3p To Regulate Elk1 Expresupporting
confidence: 77%
See 2 more Smart Citations
“…Our previous experiments confirmed that lncRNA ODSM and miR-139-3p interact with and repress each other 27 . By using the online lncRNA location prediction software lncLocator (http://www.csbio.sjtu.edu.cn/bioinf/ lncLocator/) and cell fractionation followed by quantitative reverse transcription polymerase chain reaction (qRT-PCR), we identified that lncRNA ODSM expression was located in the cytoplasm and nuclei of cells (Supplementary Fig.…”
Section: Lncrna Odsm Interacts With Mir-139-3p To Regulate Elk1 Expresupporting
confidence: 77%
“…The regulation of ELK1 by miR-139-3p relies on the 3′-UTR region of ELK1, so if the regulatory effect of the lncRNA ODSM on ELK1 depends on competitive binding to miR-139-3p, then the lncRNA ODSM should also have a regulatory effect on the 3′-UTR region of ELK1. We constructed luciferase reporter vectors containing the ELK1 3′-UTR sequence and the lncRNA ODSM sequence with a wild-type (pEX-ODSM WT) or mutated miR-139-3p binding site (pEX-ODSM MUT) as previously reported 27 , and we then transfected these vectors into cells. Overexpression of the lncRNA ODSM, but not pEX-ODSM MUT, partly blocked the mimic-139-induced reduction in luciferase activity of the ELK1 reporter vector.…”
Section: Lncrna Odsm Interacts With Mir-139-3p To Regulate Elk1 Exprementioning
confidence: 99%
See 1 more Smart Citation
“…A 2D clinostat (developed by the China Astronaut Research and Training Center, Beijing, China) was selected to simulate the unloading environment in vitro, and related experiments were performed according to the procedure described previously. 13,65 Briefly, MC3T3-E1 cells were seeded in 25-cm 2 culture flasks at a density of 5×10 5 cells per flask. After cell adherence, the culture flasks were filled with osteogenic medium, ensuring that air bubbles were removed.…”
Section: Clinorotationmentioning
confidence: 99%
“…6 HLU mice, an established model used to simulate skeletal unloading, show irreversible bone loss via the inhibition of bone formation and the promotion of bone resorption. 5,[7][8][9] In vitro experiments in ground-based facilities for simulating microgravity unloading, such as 2D clinostat, random positioning machine (RPM), rotating wall vessel (RWV) bioreactor and magnetic levitator, indicated that the dysfunction of osteoblasts caused by unloading can disturb their ability to translate mechanical loading into biochemical signals, which can partly explain the occurrence of unloading-induced bone loss, [10][11][12][13] and many intracellular signaling pathways have been reported to participate in this complex process. 5,8,14 To further understand the pathophysiology of unloading-induced bone loss and identify new biological targets, we selected 2D clinorotation and HLU models for simulating unloading conditions in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%